Tinjauan Yuridis Terkait Gugatan Nomor 284/G/Tf/2023/Ptun Jakarta Atas Peraturan Menteri Perdagangan Nomor 11 Tahun 2022 Dari Perspektif Unsur Keputusan Tata Usaha Negara - Palapessy, Carolene Agatha; Kohir, Karina; Gitta, Helga; Paselle, Enos (Journal Evidence Of Law, 2023)
The release of Minister of Trade Regulation Number 11 of 2022 then invited a lot of controversy and protests, one of which was the emergence of lawsuits from several palm oil companies including PT. Wilmar Nabati Indonesia is famous for producing Sania and Fortune cooking oils which are sold both in supermarkets and markets in Indonesia. The purpose of issuing this regulation is to overcome the phenomenon of scarce oil, because with it the price of oil will become expensive but in terms of quantity it will appear because the price is high due to the HET not being regulated in Minister of Trade Regulation Number 11 of 2022. This research was analyzed using data method techniques. descriptive qualitative with library research data collection techniques on secondary data which is then carried out by reducing and interpreting the data. The aim of this research is to review juridically the lawsuit regarding Minister of Trade Regulation Number 11 of 2022 from the perspective of the elements of state administration decisions. This Minister of Trade Regulation is appropriate to be brought to the Jakarta PTUN (State Administrative Court) by PT. Wilmar Nabati Indonesia as the plaintiff with the Minister of Trade Zulkifli Hasan as the defendant. The Minister of Trade Regulation is not worth challenging because the KTUN has given rise to legal consequences. This is based on Article 53 Paragraph (2) of Law Number 9 of 2004 concerning PTUN which states that the law can be traced through the absence of legal losses. Direct and real losses can be traced if the KTUN in question has a relationship with a person or civil legal entity.